Cerebellar cortex сhanges in posterity of female rats receiving PgE2 for induction of parturition. - Grigorieva, E. A.; Mamay, I. Y. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. The effect of birth stimulation on the brain structure still remains an unexplored issue. Objective. To determine the morphological cerebellar cortex changes in laboratory rats during the postnatal period after intravaginal injection of prostaglandin E2 for labor induction. Methods. The changes in the structure of cerebellar cortex in posterity of white syngenic rats from the 14th to the 60th day of life have been studied. Pregnant females of the experimental group were injected PgE2 in the form of a gel intravaginal to stimulate labor on the 20th day of pregnancy. The duration of pregnancy in the rats of the experimental group was 21 day, in the rats of intact group - 23-24 days after conception. The beginning of pregnancy was established by the method of vaginal smears stained with methylene blue; presence the sperm in smears was taken for 0 day of pregnancy. The cerebellum was fixed in a 10% neutral formalin solution, dehydrated in an ascending battery of ethyl spirits. 5 μm paraffin sections were stained with hematoxylin and eosin. The thickness of the molecular and granular layers of the cerebellar cortex, the number of cells of the granular layer per unit area, the number of Purkinje cells and their sizes were determined in the histological samples. Data are processed by the variation statistic method. The results are significant for p <0.05. Results. It is settled that at day 14th after birth there are no significant changes in the thickness of cerebellum molecular layer in posterity of female rats receiving PgE2 for induction of labor. From 21st to 60th day of life the thickness of the molecular layer doesn’t vary considerably in group over age and in comparison with intact group. The thickness of the granular layer tends to thinning in the experimental group compared to intact from 21st to 60st day of life. Also there is a reduction of the absolute number of cells in the granular layer per unit area from 21st to 60st day of life in experimental animals. Conclusion. Purkinje cells in the experimental and intact animals did not differ in their shape, location, size; however, there is an increase of distance between the Purkinje cells at all stages of development in experimental animals compared to the intact group.